2018
DOI: 10.1016/j.bbamcr.2018.03.013
|View full text |Cite
|
Sign up to set email alerts
|

Identification of a unique loss-of-function mutation in IGF1R and a crosstalk between IGF1R and Wnt/β-catenin signaling pathways

Abstract: IGF1R is a ubiquitous receptor tyrosine kinase that plays critical roles in cell proliferation, growth and survival. Clinical studies have demonstrated upregulation of IGF1R mediated signaling in a number of malignancies including colon, breast, and lung cancers. Overexpression of the IGF1R in these malignancies is associated with a poor prognosis and overall survival. IGF1R specific kinase inhibitors have failed in multiple clinical trials partly because of the complex nature of IGF1R signaling. Thus identify… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
14
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(15 citation statements)
references
References 34 publications
1
14
0
Order By: Relevance
“…Here, we showed that DB treatment not only suppressed colon tumorigenesis, but also CSC phenotypes. DB-medicated CSC-inhibitory effects were associated with the decreased expression of the IGF downstream oncogenic marker, mTOR/STAT3, as well as the stemness marker, β-catenin, both of which have been reported to contribute to treatment failure and the recurrence of colon cancer [ 23 , 34 , 35 ].…”
Section: Discussionmentioning
confidence: 99%
“…Here, we showed that DB treatment not only suppressed colon tumorigenesis, but also CSC phenotypes. DB-medicated CSC-inhibitory effects were associated with the decreased expression of the IGF downstream oncogenic marker, mTOR/STAT3, as well as the stemness marker, β-catenin, both of which have been reported to contribute to treatment failure and the recurrence of colon cancer [ 23 , 34 , 35 ].…”
Section: Discussionmentioning
confidence: 99%
“…In addition, IGF-IR interacts with T cell factor (TCF) and promotes the expression of β-catenin/TCF targets including cyclin D1 and axin 2 [87]. Of note, the kinase activity of IGF-IR is not required for its nuclear translocation and activation of transcription [88]. Nevertheless, the nuclear IGF-IR still acts as a kinase to phosphorylate its nuclear partners.…”
Section: Nuclear Igf-ir Regulates Gene Expressionmentioning
confidence: 99%
“…GSK3β is the major regulatory enzyme of numerous intracellular signal transduction pathways (14). Regulating GSK3β activity is able to affect the growth and apoptosis of different tumor types, including colon, lung and breast cancer (15); however, experiments on the effect of regulating GSK3β activity on tumor cell proliferation have led to contrasting results (12)(13)(14)(15).…”
Section: Introductionmentioning
confidence: 99%
“…The Wnt/β-catenin signaling pathway is associated with tumor development (15). In breast, liver, stomach, thyroid, lung and prostate cancer, as well as melanoma and other malignant tumor types, the abnormal activation of the Wnt/β-catenin signaling pathway and the downregulation of expression or the inactivation of the pathway inhibitory proteins, such as Dickkopf Wnt signaling pathway inhibitor 1 (DKKI) or Wnt inhibitory factor 1 (WIF), have been determined (15,16).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation